The effectiveness of the tax amnesty towards promoting compliance and increasing revenue inflow for Zimra - Jaka, Tinashe (Midlands State University, 2017)
The government of Zimbabwe enacted Finance Act no 2 of 2014 that introduced a tax amnesty program in order to make further provision of revenue in light of the fiscal crisis that has seen government failing to meet its expenditure. Proponents of tax amnesties point out that an amnesty may positively affect revenue and compliance. Other scholars argue that anticipation of future amnesties will result in a long term negative influence over revenue and compliance. The research sought to analyze the effectiveness of the tax amnesty introduced in October 2014 towards promoting tax compliance and raising revenue for Zimra. In order to draw a conclusion to the findings of this research a literature review and investigative research methods were employed to gather data for presentation and analysis. The major findings of the research indicate that the tax amnesty program was a failure, and this can be attributed mainly to the prevailing socio economic condition. As such recommendations from the study were provided.